Analisis TOPSIS Dalam Penentuan Rusunawa Unggul Menggunakan Aspek Hunian Keberlanjutan Berdasarkan Persepsi Penghuni - Epiphanias Simanjuntak; Mohtana Kharisma Kadri (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2025)
The application of the TOPSIS analysis method aims to determine superior rusunawa in Balikpapan City based on residents' perceptions of various aspects of sustainability. This study examines nine rusunawa in Balikpapan and identifies the existing conditions of rusunawa through four aspects of sustainability, namely environmental, social, economic, and cultural. The results of the study indicate several shortcomings in rusunawa management, such as suboptimal waste and wastewater management, lack of social and cultural facilities, and limited support for residents' independent economic activities. Through the application of TOPSIS analysis, rusunawa with the best level of sustainability was found, which is a reference for rusunawa development in the future. The proposed sustainable housing concept includes the development of renewable energy systems, improving socio-cultural facilities, and more participatory environmental management to realize sustainable housing and improve the quality of life of residents.